2019
DOI: 10.1002/mrm.27751
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation‐compensated APT and rNOE CEST‐MRI of human brain tumors at 3 T

Abstract: Purpose Relaxation‐compensated CEST‐MRI (i.e., the inverse metrics magnetization transfer ratio and apparent exchange‐dependent relaxation) has already been shown to provide valuable information for brain tumor diagnosis at ultrahigh magnetic field strengths. This study aims at translating the established acquisition protocol at 7 T to a clinically relevant magnetic field strength of 3 T. Methods Protein model solutions were analyzed at multiple magnetic field strengths to assess the spectral widths of the ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
111
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 52 publications
(118 citation statements)
references
References 61 publications
(149 reference statements)
3
111
0
Order By: Relevance
“…A prerequisite for a reliable retrospective image coregistration was the acquisition of 3D volumetric image data, which was realized by translating the snapshot‐CEST approach to 7 T. The 3D snapshot‐CEST image readout was already successfully applied for volumetric coregistration of human DGE images at 3 T . In contrast, the initial DGE‐MRI examinations in humans were only coregistered in plane due to a limited 2D image readout .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A prerequisite for a reliable retrospective image coregistration was the acquisition of 3D volumetric image data, which was realized by translating the snapshot‐CEST approach to 7 T. The 3D snapshot‐CEST image readout was already successfully applied for volumetric coregistration of human DGE images at 3 T . In contrast, the initial DGE‐MRI examinations in humans were only coregistered in plane due to a limited 2D image readout .…”
Section: Discussionmentioning
confidence: 99%
“…Images were acquired using a 3D spiral‐centric‐reordered gradient‐echo image readout (i.e., the snapshot‐CEST approach by Zaiss et al). Image‐readout parameters were adapted from the previously optimized snapshot‐CEST versions at 9.4 T and 3 T and set to: FOV = 220 × 179 × 54 mm 3 , image matrix = 128 × 104 × 18, resolution = 1.7 × 1.7 × 3 mm 3 , GRAPPA acceleration factor = 3, TE = 2.13 ms, TR = 4.22 ms, bandwidth = 560 Hz/pixel, flip angle = 6°, and elongation factor = 0.6. Note that the two outer slices on each side must be rejected due to aliasing artifacts in the slice direction, resulting in an effective number of 14 slices.…”
Section: Methodsmentioning
confidence: 99%
“…An overview of the presented data processing pipeline is given in Figure . In vivo Z‐spectra are acquired at 3T and evaluated by conventional methods (PCA denoising, Lorentzian fitting). The obtained results are used to train a deep neural network to directly map from raw Z‐spectra to Lorentzian parameters, yielding CEST contrast maps in ~1 s where conventional evaluation takes ~10 min.…”
Section: Methodsmentioning
confidence: 99%
“…The Z‐spectra were spectrally de‐noised by principal component analysis (PCA) following the approach of Breitling et al, keeping only the principal components suggested by the median criterion (Supporting Information Table ). To isolate CEST effects, a four‐pool Lorentzian fit model according to Goerke et al was used to fit the direct water saturation (DS), semi‐solid magnetization transfer (MT), amide proton transfer (APT), and relayed NOE peaks, using the model equationZΔω=c-LDS-LAPT-LNOE-LMT,with a constant c, the direct saturation poolLitalicDS=ADS1+)(Δω-normalδDSnormalΓDS/22,and the other poolsLi=Ai1+)(Δω-normalδDS-normalδinormalΓi/22,iAPT,NOE,MT,with amplitudes A i , full‐width‐at‐half‐maximum Γ i , and peak positions δ i . This model has 10 free parameters in total (4 amplitudes A i , 4 widths Γ i , water peak position δ DS , and constant c ), as the positions of APT, NOE, and MT peaks were fixed at +3.5 ppm, −3.5 ppm, and −2.5 ppm relative to the water peak position, respectively, and were therefore not treated as free parameters.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation